Behind smoke and mirrors: On the alleged recapitalization of Europe's banks - Jakob Vestergaard; María Retana (Danish Institute for International Studies (DIIS), 2013)
When publishing the results of the recapitalization exercise, the European Banking Authority reported that European banking had been successfully recapitalized and was now in a much stronger position, with a much strengthened capital base and overall resilience. 'European banks have made significant progress in boosting their capital positions and in strengthening the overall resilience of the European banking system', said Andrea Enria, Chairman of the European Banking Authority. 'More than 200bn has been injected into the European banking system', he continued, and European banks 'are now in a better shape to finance the real economy' (EBA 2012c: 1). Our analysis questions this assessment. The recapitalization orchestrated by the European Banking Authority was based on a capital assessment methodology that has been subject to considerable scholarly criticism.1 The methodology of basing regulatory capital requirements on risk-weighted assets is a less reliable indicator of banks' soundness and resilience than much simpler ratios of capital to total assets (Acharya et al. 2011). The paper therefore compares the assessments undertaken by EBA - all of which are based on risk-weighted assets - with data on leverage ratios, defined as equity capital to total assets.
Keywords: 300